Immobilization of biosorbent in hydrogel as a new environmentally friendly fertilizer for micronutrients delivery. (20th December 2019) - Skrzypczak, D.; Witek-Krowiak, A.; Dawiec-Liśniewska, A.; Podstawczyk, D.; Mikula, K.; Chojnacka, K.
Abstract: The aim of this work was to study the use of alginate-carboxymethyl cellulose-eggshell biocomposites as a material with controlled release of Cu 2+ ions. The composition of biocomposites was optimized with Response Surface Methodology (5.0 wt% sodium alginate, 1.2 wt% carboxymethyl cellulose, 10.0 wt% eggshells). Physicochemical properties of biocomposites, kinetics and equilibrium of copper(II) ion sorption on structures were investigated. The General Rate Law model best described the kinetics data and the values of kinetic rate constants were 0.259, 0.358 min −1 for wet and dry capsules. The description of the sorption kinetics was also presented with the Weber-Morris diffusion model, which indicated a multi-stage process. The maximum sorption capacities for wet and dry biocomposites were 281 and 49 mg g −1 . The composites presented a slow release of ions in the model soil solution (9 wt%/14 days). Studied biocomposites have a good potential as controlled release fertilizers fitting into the concept of sustainable development and precision agriculture. The new fertilizer formulations have the potential to by used as a new type of slow-release fertilizer that delivers micronutrient ions according to the plants uptake pattern with minimization of losses into the environment. Graphical abstract: Image 1 Highlights: The sorption capacity of the biocomposites was investigated. The sorption process is three-stage and has been described with the Weberr-Morris diffusion model. The equilibrium data has been described by the Langmuir, Freundlich and Sips models (Qmax 49 mg g −1 ).